Deconstructing climate justice in indonesia's climate mitigation legal policy: A theoretical analysis of distributive and procedural justice in the Carbon Economic Value (NEK) regulation - Wahyu Fahmi Rizaldy (Priviet Social Sciences Journal, 2026)
Presidential Regulation No. 98 of 2021 “Carbon Economic Value” gives the first market-based instrument in the legal politics of Indonesia mitigation of climate change. In relation to this, the regulation hopes to accelerate target emissions. However, it also under climate justice implications in relation to the most vulnerable, specifically Indigenous Peoples (Masyarakat Hukum Adat/MHA). This research aims to dismantle the climate justice within the legal politics of NEK Regulation. This research is based on normative legal research methods where the author employs a statute, a conceptual approach, and a critical approach. This research is concerned with the two pillars of justice: distributive and procedural. The research findings show, first, that the legal politics of NEK distributive justice is to a large degree narrowly defined where the focus is on the ‘money’, ‘distribution’, and ‘rights’, and these ‘rights’ are the corporate permits. Perhaps worse, there are likely neo-disparities in the economic benefit-sharing to the Indigenous Peoples relative to the ecological burden-sharing. Second, in respect to the NEK regulation and procedural justice, particularly around the Free, Prior and Informed Consent (FPIC) concept, procedural justice in its normative assessment sees it as the completion of an administrative ritual. Such representation runs a high risk of becoming tokenism, which co-opts and undermines the real rights of Indigenous Peoples concerning carbon governance. This study finds that the NEK Regulation, as it currently stands, favors the efficiency of markets over justice in a substantive form, which illustrates the need to refocus the legal politics of mitigation on climate justice as a cornerstone.